Dust control and air cleaning - Dorman, Richard George (International series of monographs in heating, ventilation, and refrigeration, 1974)
Dust Control and Air Cleaning covers various areas of concerns in the management of airborne particles and air sanitization. The title provides a comprehensive coverage of the methods in regulating air quality.